Morave Mt Oligocene-Middle Miocene succession of Albanian-Thessalian Basin - Pashko, Pandeli (Bulletin of the Geological Society of Greece, 2018)
The Morava Mountain Oligocene-Middle Miocene molasse deposits take part in the Albanian-Thessalian Basin, which developed NW-SE from eastern Albania to Thessaly in Greece, where it is called as Mesohellenic Basin. The 4.5 km thick basin infill is subdivided into three molasse cycles separated by two regional unconformities at the Eocene/Oligocene and Aquitanian/Burdigalian boundaries. The Morava Mountain Oligocene-Middle Miocene molase, ~ 3500 m thick, represents an exposed continuous, rich in fossil fauna succession. Six stratigraphic sections were studied and measured.